Porcelain crabs from Brazil (Crustacea: Decapoda: Anomura: Porcellanidae) - Ferreira, Luciane Augusto De Azevedo; de Melo, Gustavo Augusto Schmidt (Zootaxa, 2016)
Twenty species of porcelain crabs are reported on the basis of material collected from Brazilian coasts. Considering the lack of systematic studies comprehending the Brazilian porcellanids, the present work presents a review of the regional species based on the current taxonomic information. New records, information about variation between specimens and a taxonomic discussion are given for porcellanid crabs from Brazil.